Ribosomal protein S14 transcripts are edited in Oenothera mitochondria. - Schuster, W (1990)
The gene encoding ribosomal protein S14 (rps14) in Oenothera mitochondria is located upstream of the cytochrome b gene (cob). Sequence analysis of independently derived cDNA clones covering the entire rps14 coding region shows two nucleotides edited from the genomic DNA to the mRNA derived sequences by C to U modifications. A third editing event occurs four nucleotides upstream of the AUG initiation codon and improves a potential ribosome binding site. A CGG codon specifying arginine in a position conserved in evolution between chloroplasts and E. coli as a UGG tryptophan codon is not edited in any of the cDNAs analysed. An inverted repeat 3' of an unidentified open reading frame is located upstream of the rps14 gene. The inverted repeat sequence is highly conserved at analogous regions in other Oenothera mitochondrial loci.